La restauration d’une œuvre monumentale de Lucien Simon - Nico Broers; Eleni Markopoulou (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This short account details the issues raised during the conservation of a monumental painting intended for a theme museum with inadequate exposition space.